Phase transition and switchable dielectric behaviours in an organic–inorganic hybrid compound: (3-nitroanilinium)2(18-crown-6)2(H2PO4)2(H3PO4)3(H2O) - Yang Liu (Royal Society Open Science, 2018)
An organic–inorganic hybrid compound with an extensive three-dimensional (3D) crystal structure, (3-nitroanilinium)2(18-crown-6)2(H2PO4)2(H3PO4)3(H2O) (1), was synthesized under slow evaporation conditions. Differential scanning calorimetry measurements indicated that 1 underwent a reversible phase transition at ca 231 K with a hysteresis width of 10 K. Variable-temperature X-ray single-crystal diffraction revealed that the phase transition of 1 can be ascribed to coupling of pendulum-like motions of its nitro group with proton transfer in O–H···O hydrogen bonds of the 3D framework. The temperature dependence of its dielectric permittivity demonstrated a step-like change in the range of 150–280 K with remarkable dielectric anisotropy, making 1 a promising switchable dielectric material. Potential energy calculations further supported the possibility of dynamic motion of the cationic nitro group. Overall, our findings may inspire the development of other switchable dielectric phase transition materials by introducing inorganic anions into organic–inorganic hybrid systems.